2019
DOI: 10.23887/jstundiksha.v8i2.21197
|View full text |Cite
|
Sign up to set email alerts
|

Sistem Pendukung Keputusan Pemberian Beasiswa Bidikmisi Menggunakan Metode Saw-Topsis Di Stahn Mpu Kuturan Singaraja

Abstract: Penelitian ini bertujuan untuk membuat sebuat sistem pendukung keputusan (SPK) dalam memberikan rekomendasi calon mahasiswa penerima bantuan beasiswa bidikmisi. Studi kasus penelitian ini adalah Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja. Adapun metode pendukung keputusan yang digunakan adalah kombinasi dari metode SAW (Simple Additive Weighting) dan TOPSIS. Data penelitian yang digunakan adalah 30 calon mahasiswa penerima beasiswa dan dicari 10 orang rekomendasi. Kriteria penilaian yang digunakan adalah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Sistem itu digunakan untuk membantu pengambilan keputusan dalam situasi yang semiterstrutur dan situasi yang tidak terstruktur, dimana tak seorang pun tahu secara pasti bagaimana keputusan seharusnya dibuat. [4] Sistem ini digunakan untuk membantu pengambilan keputusan dalam situasi yang semiterstruktur dan situasi yang tidak terstuktur, dimana tidak seorangpun tahu secara pasti bagaimana keputusan seharusnya dibuat. [5]…”
Section: Sistem Pendukung Keputusanunclassified
“…Sistem itu digunakan untuk membantu pengambilan keputusan dalam situasi yang semiterstrutur dan situasi yang tidak terstruktur, dimana tak seorang pun tahu secara pasti bagaimana keputusan seharusnya dibuat. [4] Sistem ini digunakan untuk membantu pengambilan keputusan dalam situasi yang semiterstruktur dan situasi yang tidak terstuktur, dimana tidak seorangpun tahu secara pasti bagaimana keputusan seharusnya dibuat. [5]…”
Section: Sistem Pendukung Keputusanunclassified
“…Make a decision matrix in equation 1 for the problem to be solved with the following conditions [14]:…”
Section: Calculation Of Topsismentioning
confidence: 99%
“…However, this method is less effective in producing weights that take into account the relationship between criteria (Septy & Devega, 2022). According to (Heriawan & Subawa, 2019) combining the TOPSIS method with other methods such as SAW is needed for weighting. The SAW method was chosen because this method can provide a more accurate assessment by considering the criteria value of the weight of each predetermined preference, and normalizing the matrix by taking into account the value of the attributes, including the benefit and cost values of the criteria to be used (Heriawan & Subawa, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to (Heriawan & Subawa, 2019) combining the TOPSIS method with other methods such as SAW is needed for weighting. The SAW method was chosen because this method can provide a more accurate assessment by considering the criteria value of the weight of each predetermined preference, and normalizing the matrix by taking into account the value of the attributes, including the benefit and cost values of the criteria to be used (Heriawan & Subawa, 2019). Another study conducted by (Putu & Sudarsana, 2022) concluded that the combination of SAW and Topsis methods was able to provide better results than using only one method, namely SAW or TOPSIS (Putu & Sudarsana, 2022).…”
Section: Introductionmentioning
confidence: 99%